Faktor Terjadinya Sengketa Tukar Menukar Tanah di Desa Teloyo Kabupaten Klaten - Isti Ary Wardani; Reni Anggriani (Universitas Muhammadiyah Yogyakarta, 2023)
Land problems often occur in the Republic of Indonesia, especially regarding the ownership of land rights. Each ownership of land rights must be accompanied by proof of ownership, namely a land certificate. If the ownership of the land is still unclear, then the land is still in dispute. As an example of the case that occurred in Teloyo Village, Wonosari District, Klaten Regency, the main problem in this case was the unclear status of the land because the land transfer process by means of land swaps had not been fully resolved so that there was an acknowledgment that the land belonged to an individual. The problem studied in this study is regarding the factors that cause land disputes through the process of exchanging village treasury land with privately owned land in Teloyo Village, Klaten Regency. This study uses a qualitative approach to the type of empirical juridical research. The purpose of this research is to find out what are the factors that cause land ownership disputes in the transfer of land ownership rights through the land exchange process. The data sources of this research are primary data and secondary data. Primary data obtained from the results of interviews conducted with informants. Secondary data is obtained from laws and scientific writings that support research. In this study it was concluded that one of the factors causing land disputes was inadequate regulation regarding the process of transferring property rights that occurred in Teloyo Village.